IMPLEMENTASI PEMBELAJARAN BERBASIS CASE METHOD DALAM MENINGKATKAN KEMAMPUAN BERKOMUNIKASI DAN CRITICAL THINKING MAHASISWA - Deci Ririen; Irawati Irawati (Jurnal Dedikasi Pendidikan, 2023)
: Participatory and collaborative learning systems, including case-based learning methods, are an alternative to adapt to the developments and challenges of the 21st century, which requires students to master the skills of communication and critical thinking. The purpose of this study is whether there are differences in students' communication skills and critical thinking through the application of case-based learning methods. How is the relationship between communication skills and critical thinking. This type of research is a quasi-experimental research. 2 groups of students who took the statistics course II semester IV were the research samples. The data analysis technique used independent t-test with prerequisite tests, namely homogeneity test and data normality test. As well as a correlation test to see the relationship between students' communication skills and critical thinking with the help of SPSS version 24. The results showed that there was an increase in students' communication skills in classes using case-based learning methods. There is an increase in students' critical thinking in classes that use case-based learning methods. There is a strong relationship between communication skills and students' critical thinking.